Isolation and identification of nucleosides/nucleotides raising testosterone and NO levels of mice serum from Chinese chive (Allium tuberosum) leaves. (5th November 2018) - Gu, Shuang; Wang, Xiangyang; Zhou, Rong; Huang, Jianying
Abstract: Our previous study found that Chinese chive could significantly ( p  < 0.01) raise testosterone and nitric oxide (NO) levels in mice serum. However, the specific functional components of this traditional remedy are still unknown. In order to isolate and identify the active constituents from Chinese chive for enhancing testosterone and NO levels, the Chinese chive leaves were extracted by petroleum ether, ethyl acetate, n ‐butanol and water respectively. Results indicated that the n ‐butanol extract had a significant effect on NO and testosterone blood levels. Subsequently, n ‐butanol extract was further isolated by D101 macroporous adsorption and eluted with 50% ethanol and then isolated by Sephadex LH‐20 and preparative high‐performance liquid chromatography to obtain nucleosides. The fraction eluted with 70% ethanol was further isolated by RP‐18 and pre‐HPLC to obtain nucleotides. Four novel compounds were identified, and their effects on testosterone and NO levels of male mice were evaluated. Results showed that nucleotides, especially the adenosine in Chinese chive leaves, increased serum testosterone and NO levels in male mice, which had not been reported before. This finding might bring into perspective the treatment strategy for those doctors who treat hormone deficiencies, and might be suitable for using in functional food.